2016
DOI: 10.2147/ppa.s111537
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of patient safety culture among Malaysian retail pharmacists: results of a self-reported survey

Abstract: BackgroundPatient safety is a major public health issue, and the knowledge, skills, and experience of health professionals are very much essential for improving patient safety. Patient safety and medication error are very much associated. Pharmacists play a significant role in patient safety. The function of pharmacists in the medication use process is very different from medical and nursing colleagues. Medication dispensing accuracy is a vital element to ensure the safety and quality of medication use.Objecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
45
7
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(65 citation statements)
references
References 30 publications
11
45
7
2
Order By: Relevance
“…The average PRR for the patient safety culture (74.7%) in the Abu Dhabi Emirate is more than that in previous studies performed in Taiwan, China, Malaysia and the USA . The result suggested that the significance of the support of the values of patient safety in the community pharmacy practice is realised by the community pharmacists in Abu Dhabi.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…The average PRR for the patient safety culture (74.7%) in the Abu Dhabi Emirate is more than that in previous studies performed in Taiwan, China, Malaysia and the USA . The result suggested that the significance of the support of the values of patient safety in the community pharmacy practice is realised by the community pharmacists in Abu Dhabi.…”
Section: Discussionmentioning
confidence: 57%
“…As a part of healthcare providing system, community pharmacies continually exert great efforts in order to improve safety and quality, and there is an increasing recognition of the value of establishing a culture of patient safety . In developing countries, medical practitioners are the only personnel who have the legal right of drug prescription . However, pharmacists play a significant role in prescription screening and communication with patients to minimise the risk of medication error while increasing patient safety .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As there was interval between the study implementation and literature publication, we took the survey period as the time when the questionnaire was used, rather than when the literature was published. The initial version of SAQ was developed in 2002 by Bryan Sexton, Eric Thomas, and Bob Helm Reich with funding from the Robert Wood Johnson Foundation and Agency for Healthcare Research and Quality of the USA, the psychometric properties was reported in 2006 . There were 16 studies that reported the survey period, among which three surveys were performed before 2006, ranging from 2002 to 2006.…”
Section: Resultsmentioning
confidence: 99%